Thermal and Mechanical Performance of 3-Phase Polymer Composite Panels for Structural Applications - Muhammad Zubair Jilani; Zulfiqar Ahmad Rehan; Zuhaib Ahmad; Madeha Jabbar; Yasir Nawab; Khubab Shaker (International Journal of Polymer Science)
The objective of this study is to establish a conceptual framework for fiber-reinforced polymer composite (FRPC) panels designed for structural purposes through the incorporation of a third phase (fillers). The present investigation was aimed to design and fabricate 3-phase polymer composite panels that offer enhanced thermal insulation and strength while maintaining low material and labor expenses. Two types of fibrous reinforcements (jute fabric and glass fabric) of different origins were used as reinforcement; polypropylene (PP) was used as the matrix, and microcrystalline cellulose (MCC) was used as particle reinforcement material. The composite materials were fabricated with different MCC concentrations (0, 2 wt%, and 4 wt%), using a hot compression molding technique. It was found that MCC helped to enhance the mechanical performance of the composite panels, while the thermal conductivity showed a slight reduction due to lower concentrations of MCC used. For polypropylene/glass (PPG) composites, thermal conductivity was reduced from 0.214 to 0.193 W/m·K by the addition of 4% MCC fillers. Similarly, for polypropylene/jute (PPJ) composites, it was reduced from 0.14 to 0.126 W/m·K by 4% MCC fillers. The Charpy impact strength of both PPG and PPJ composites was enhanced by the addition of fillers, and the effect was more significant in the case of PPG (increased from 24.83 to 43.98 kJ/m2 for 4% fillers). Cost analysis of the composite panels was also done, showing PPJ panels to be slightly cheaper as compared to PPG. The findings indicate that the developed composite panels have the potential to serve as partitioning as well as the outer shield of the building due to their effective thermal and mechanical properties.